“INTERNATIONAL CUISINE, COOKING VERBS, KITCHEN’’ (Ustozlar uchun, 2026)
This article examines the importance of international cuisine in the process of learning English vocabulary. It focuses on the role of cooking verbs and kitchen items in expanding students’ vocabulary and improving their communicative skills. Learning about different dishes from various countries helps students not only understand new words but also become familiar with different cultures. In addition, discussing favorite foods and cooking processes encourages active participation in the classroom. The study shows that using food-related topics in language teaching can make learning more interesting, practical, and effective for students.